Consumer Participation in Co-creation: An Enlightening Model of Causes and Effects Based on Ethical Values and Transcendent Motives - Martínez-Cañas, Ricardo; Ruiz-Palomino, Pablo; Linuesa-Langreo, Jorge; Blázquez-Resino, Juan J. (Frontiers in Psychology, 2016)
In the highly interconnected modern world, the role of consumers has changed substantially due to their collaboration with companies in generating ideas, products, and services, as well as their increasing engagement with social values. Specifically, consumer participation has become key to the development of successful products and services. With an integrative review of research into value co-creation and ethics, this article proposes a conceptual model in which consumers’ ethical values and transcendent motivations encourage their engagement in co-creation activities. In this new paradigm, the co-creation process can be a means to emphasize the social and moral aspects of co-creating. This article identifies important value benefits attained by both companies and consumers after consumers engage in co-creation activities, and highlights that these benefits increase when ethical products are the object of these co-creation activities. It also notes the important, supportive role of the Marketing 3.0 paradigm and Web 3.0 tools to initiate the co-creating process. All these insights have notable implications for both research and managerial practice.